The impact of information sources on COVID-19 vaccine hesitancy and resistance in sub-Saharan Africa - Osuagwu, U.L.; Mashige, K.P.; Ovenseri-Ogbomo, G.; Envuladu, E.A.; Abu, E.K.; Miner, C.A.; Timothy, C.G.; Ekpenyong, B.N.; Langsi, R.; Amiebenomo, O.M.; Oloruntoba, Richard; Goson, P.C.; et al. (BMC, 2023)
Background: Vaccination remains the most powerful weapon against the emergence of new variants of coronavirus (COVID-19). However, false information about COVID-19 vaccines through various platforms including social media remains a major threat to global public health. This study examined the impact of information sources on COVID-19 vaccine hesitancy and resistance in sub-Saharan Africa (SSA). Methods: A validated web-based cross-sectional study was conducted from 14 March to 16 May 2021, and was administered in both French and English to 2572 participants aged 18 years and over. Data on sociodemographic characteristics, medical and vaccination history, and the information sources (mainstream media and social media) used by the participants during the pandemic were obtained. There were three main outcomes: The vaccinated group were those who responded in the affirmation (Yes) to the question of whether they have been vaccinated against COVID-19. Those who responded ‘not sure’ or ‘no’ to the question were then asked if they were willing to be vaccinated when the vaccine became available in their home countries. The responses to this follow-up question were used to derive the second and third outcome variables of ‘vaccine hesitancy’ and ‘vaccine resistance’, respectively. A series of logistic regression analyses were used to examine the impact of information sources on the three main outcomes. Results: The prevalence of COVID-19 vaccine hesitancy among the participants was lowest among newspaper readers (42%) and highest among TV (72%) and social media users (73%). The prevalence of COVID-19 vaccine-resistance was also lowest among newspaper readers (37%) but highest among social media users (87%). Multivariate analyses revealed that compared to those who did not use these information sources, SSA participants who relied on the radio (aOR 0.83, 95%CI = 0.70, 0.99), TV (aOR 0.80, 95%CI = 0.65, 0.97) and social media (aOR 0.79, 95%CI = 0.65, 0.97) for information during the pandemic were less likely to be hesitant towards taking the vaccines. However, social media users (aOR 2.13, 95%CI = 1.62, 2.80), those who watched TV (aOR 1.40, 95%CI =1.08, 1.80), relied on healthcare workers (HCWs: aOR 1.32, 95%CI = 1.07, 1.63) and families/friends (aOR 1.31, 95%CI = 1.06, 1.61) for COVID-19 related information during the pandemic were more likely to resist taking the COVID vaccines in this study. Participants who relied on the newspaper for information during the pandemic were less likely to resist the vaccines (aOR 0.77, 95%CI = 0.62, 0.95) compared to non-readers of a newspaper. Conclusion: We found that all six information sources except radio were strong predictors of the resistance towards COVID-19 vaccination. Further research on how these channels can be used to improve the availability of reliable healthcare information is needed. Investments in these resources will protect people and empower them to make appropriate choices about their health.